Principios de igualdad procesal y tutela judicial efectiva en delitos no flagrantes de violencia contra la mujer. - Conde Flores, Heydi Cristina (2025)
This thesis explores the relevance and applicability of the principles of procedural equality and effective judicial protection in crimes of violence against women and its main purpose is to determine whether the organs of justice in Ecuador guarantee these principles towards the defendant with a correct application and interpretation of the laws, since there are conflicts of partiality due to the social impact and gender perspective that these crimes cause; Procedural equality implies that both parties have the same opportunities to present evidence and arguments without imbalances that prejudice any of the parties, and effective judicial protection guarantees the right of the defendant to a solid defence. This study adopts a legal-analytical approach and employs the dogmatic method, allowing a deep analysis of the constitutional principles; this is done through the review of real cases, the application of interviews and surveys to professionals in the field, and relevant jurisprudence and doctrine. The research concludes that there is a judicial conflict in the application of these principles due to several factors, such as the social influence that affects judges and prosecutors, the difficult access to a defence due to lack of resources, the improper use of protective measures by the alleged victims, and the excessive dissemination of information by the media, breaking into important constitutional rights for the defendant.